A Brief History of Traditional Indian Medicine: In Particular, Yoga and Siddha Systems of Medicine Part 1 – WHY Indian Medicos Need to Know of the Rich Medical Heritage of Bharat - An Eye-opener - Hiramalini Seshadri; Divya Seshadri (NMO Journal)
A brief history of Traditional Indian Medicine, in particular Yoga and Siddha system of medicine, is presented as a four-part series including Part 1 – WHY Indian medicos need to know of the rich medical heritage of Bharat; an eye-opener, Part 2 – Evidence-based Ancient History of India that is Bharat revisited, Part 3 – A brief on the knowledge level of ancient India and knowledge codified under Yoga, pertaining to optimum health and maximising human potential and Part 4 – A brief on the Siddha system of medicine, including their knowledge level and the Siddha contribution to medical education in the ancient world. India’s rich medical heritage has been kept away from India and the world in general by a distorted colonial narrative. This article attempts to give a little glimpse to Indian medicos.